Evaluation of cold storage potential and shelf-life of new 'hass' type avocado selections - Machipyane, Pheladi Bridgette (My University, 2017)
The current South African ‘Hass’ type avocado cultivars are inadequate to enhance competitiveness, cultivar diversity and profitability. In an effort to ensure competitiveness and maintain sustainability, the Agricultural Research CouncilInstitute for Tropical and Subtropical Crops (ARC-ITSC) as one the South African Avocado Industry’s (SAAI) main stakeholder, has bred and selected new superior ‘Hass’ type avocado selections. However, the cold storage potential and associated physico-chemical ripening properties of these selections (‘Jalna’, ‘OA 184’ and ‘Balboa’) have not been documented. Therefore, the objective of this study was to evaluate the effect of cold storage on internal and external physico-chemical ripening variables of the new ‘Hass’ type avocado selections. New ‘Hass’ type avocado fruit maturity was evaluated using moisture content, thereafter, harvested, sorted, graded and stored under two temperature regimes (2.0°C and 5.5°C) for 28 days to simulate export conditions. The experiment was a completely randomised factorial design with three treatment factors; temperature regimes (2.0°C and 5.5°C), days to ripening and ‘Hass’ type avocado selections fruit and control (commercial ‘Hass’) replicated three times. After withdrawal from cold storage, fruit were ripened at ambient temperature and evaluated for electrical conductivity, external chilling injury, fruit water loss, skin colour change, ripening percentage, firmness, respiration rate and seed:fruit weight ratio. Results indicated that treatment factors had no significant effect on moisture content (P=0.733) and chilling injury (P=0.776). Treatment factors had a significant effect on electrical conductivity (P=0.004), skin colour parameters; eye colour (P<0.001), hue angle (P<0.001), lightness (P=0.011) and chroma (P=0.042). Selection ‘Jalna’ fruit started changing colour whilst in storage (2.0°C and 5.5°C). Furthermore, ‘Hass’ type avocado selection fruit followed a declining pattern for lightness, chroma and hue angle in agreement with commercial ‘Hass’. Moreover, results indicated that treatment factors had a significant effect (P<0.001) on respiration rate, fruit firmness, ripening percentage and seed:fruit weight ratio. Selection ‘Jalna’ and ‘OA 184’ desynchronised mesocarp softening with exocarp due to genetically non-softening exocarp. Treatment factors had no significant effect (P=0.998) on fruit water loss during ripening. Selection ‘OA 184’ fruit showed export potential due to its good storage, ripening physico-chemical and shelf-life properties. Studies on cold sterilisation would add more value on generated scientific information, as such would enable the SAAI to gain access to high paying export markets. In addition, the selections should be planted and evaluated in other avocado producing region
Thesis (M.Sc. Agriculture (Horticultrure)) -- University of Limpopo, 2017
Keywords: Days to ripening; Electrical conductivity; Firmness; Fruit water loss; Physico-chemical variables; Respiration rate; Ripening percentage; Seed:fruit weight ratio; Skin colour change; Fruit -- Storage; Fruit -- Ripening; Avocado; Cold storage